2015
DOI: 10.1186/s40644-015-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of 18FDG PET/CT in colorectal cancer patients with liver metastases: a meta-analysis

Abstract: BackgroundThe role of 18-fluorodeoxyglucose positron emission tomography CT (18FDG PET/CT), as a prognostic factor for survival in colorectal cancer patients with liver metastases, is still controversial. We sought to perform a meta-analysis of the literature to address this issue.MethodsA systematic literature search was performed to identify the studies that associated 18FDG PET/CT to clinical survival outcomes of patients with liver metastases. Methodological qualities of the included studies were also asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…In this meta-analysis, STATA statistics software (Version 12.0) and RevMan 5.3 software were used to calculate the pooled hazard ratios (HRs) and odds ratios (ORs) with their 95% CIs, respectively. DFS, PFS, and RFS were merged as event-free survival (EFS) [18,19]. Statistical heterogeneity was evaluated by the Q-statistic test and I 2 statistic test, and two different models were selected according to the heterogeneity level; if there was significant heterogeneity (P Q < 0.1 or/and I 2 >50%), then the randomeffects model was used; otherwise, the fixed-effects model was applied for nonsignificant heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, STATA statistics software (Version 12.0) and RevMan 5.3 software were used to calculate the pooled hazard ratios (HRs) and odds ratios (ORs) with their 95% CIs, respectively. DFS, PFS, and RFS were merged as event-free survival (EFS) [18,19]. Statistical heterogeneity was evaluated by the Q-statistic test and I 2 statistic test, and two different models were selected according to the heterogeneity level; if there was significant heterogeneity (P Q < 0.1 or/and I 2 >50%), then the randomeffects model was used; otherwise, the fixed-effects model was applied for nonsignificant heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other reports have indicated that SUV reflects the therapeutic effect after chemotherapy . Furthermore, Xia et al reviewed the application of FDG‐PET and found that SUV was correlated with prognosis after treatment in 867 cases of CRLM from 15 studies. Although most of these reports have indicated that SUV is related to prognosis after chemotherapy, a few retrospective studies have revealed that SUV is related to the postoperative prognosis of CRLM.…”
Section: Discussionmentioning
confidence: 99%
“…72,73 In patients with liver metastases treated with chemotherapy, reduction in FDG-uptake indicates improved prognosis. 74 As yet there is no threshold to allow decision-making based on these data, but novel methods for analyzing PET data may further improve prognostication using this functional imaging tool. 75…”
Section: Metabolic Imagingmentioning
confidence: 99%